Upaya Bhabinkamtibmas Dalam Rangka Menanggulangi Tindak Pidana Curanmor - Saputra, Ammar Edwin (Indonesian Journal of Police Studies, 2020)
This study aims to analyze the efforts of Bhabinkamtibmas in the context of tackling criminal acts of fraud in the Gempol police precinct in the Cirebon district police. This study uses a qualitative approach with field research methods. Data analysis with data reduction, data presentation, and drawing conclusions. The results of the study 1) The implementation of Bhabinkamtibmas in the context of overcoming criminal acts of fraud in the jurisdiction of the Gempol Sector Police has referred to Article 26 of the Republic of Indonesia National Police Chief Regulation Number 3 of 2015 concerning Community Policing. Bhabinkamtibmas Gempol Police Station is still focused on visiting / sambang, guiding and counseling in the field of law, and disseminating information about the threat of crime of fraud. Activities which are also a function of Bhabinkamtibmas, such as encouraging the implementation of the social security system, mobilizing positive community activities and coordinating with village officials have not been carried out continuously. 2) Factors that influence the implementation of Bhabinkamtibmas in dealing with criminal acts of curanmor, can be grouped into factors of Bhabinkamtibmas officers and other factors outside Bhabinkamtibmas. Factors from Bhabinkamtibmas officers include the limited number of personnel, the lack of vocational Binmas, limited budget, limited official vehicles. Other factors outside Bhabinkamtibmas include the support of community leaders, traditional leaders and religious leaders as well as the wide legal area of ​​the Gempol police station. The conclusion in this study, namely the efforts of Bhabinkamtibmas in the context of overcoming criminal acts of curanmor in the jurisdiction of Gempol Sector Police have been in accordance with applicable laws and regulations, although they have not been able to prevent the occurrence of criminal acts of curanmor.